2011 Delmar Nurse's Drug Handbook - Spratto, George; Woods, Adrienne L. (Delmar Cengage Learning, 2011)
A resource for the most important drug information with over 1,000 of the latest and most common FDA-approved drugs. Each entry provides a wealth of facts concerning drug action, dosage, interactions, and contraindications. It also provides guidelines for administration of drugs, communication with clients, and nursing considerations